Pendekatan Tourism Business District Pada Pengembangan Kawasan Pariwisata Terpadu Di Kota Tomohon - Rantung, Alsa Margareth; Egam, Pingkan Peggy; Tarore, Raymond (Fraktal : Jurnal Arsitektur, Kota dan Sains, 2024)
Tourism is one of the fastest growing sectors of the economy and has an impact on various other sectors. Tourismdevelopment links all components into an integrated tourism plan. Tomohon City is an area where community activitiesare concentrated by concentrating services and developed into a tourist destination connected to the function of thecity's business center. So that tourism is presented along with the attractiveness of the city and its landscape. Thepurpose of this research is to identify factors that influence tourism development and map the category of tourist areasthrough the Tourism Business District (TBD) concept approach with qualitative descriptive research methods. Based onthe results of the study, it was found that there are four factors that influence tourism development: public infrastructure,public facilities, tourism facilities and accessibility that have an impact on the carrying capacity of tourist attractions. Thisresults in four categories of tourism potential, there are 10 very high potential tourism, 9 high potential tourism, 12medium potential tourism, and 12 low potential tourism. Based on the results of the analysis, there are 5 zones with 4categories of tourism district, first artificial, religious and historical based tourism district divided into 2 zones in theTomohon Highway corridor, the second is artificial and history based tourism district in West Tomohon, the third isartificial and nature based tourism district in East Tomohon, and fourth agrotourism and artificial based tourism district inNorth Tomohon. Keywords : Tourism Business District Concept, Tomohon City, Tourism